Detection of uterine abnormalities using three-dimensional vaginal ultrasound in infertile women undergoing assisted reproductive techniques - Huda Ali Hussaini; Asmaa Kadhim Gatea; Suhaila F. Al-Shaikh (Medical Journal of Babylon)
Abstract Background: Uterine shape and cavity abnormalities form a common cause of subfertility, for which thorough assessment is considered as a core part in infertility evaluation. A variety of modalities (invasive and none invasive) such as hysterosalpingography, transvaginal sonography, diagnostic hysteroscopy, two-dimensional hysterosonography, and three-dimensional hysterosonography can be used for the diagnosis of uterine abnormalities. Objectives: To address the detection rate of uterine and endometrial abnormalities in infertile women undergoing assisted reproductive techniques (ART) using three-dimensional vaginal ultrasonography. Materials and Methods: A cross-sectional observational study that involved 211 subfertile women who were arranged to undergo ART for different causes of infertility. After taking their verbal consent for participation in this study, all women examined by 2D vaginal U/S for initial assessment of their pelvic anatomy then followed by three-dimensional U/S with or without saline infusion for further assessment of the uterine and endometrial cavity morphology. Women with ultrasound detected endometrial abnormalities further underwent hysteroscopic assessment, histopathological specimens were taken and were treated as recommended by their gynecologist. Results: Twenty-two percent of the studied group discovered to have uterine and/or endometrial abnormalities including endometrial polyps and uterine myomas are the most commonly detected abnormalities while congenital uterine malformation detected in 3.8% of the total patients using three-dimensional ultrasonography. Conclusion: Uterine and endometrial abnormalities are common in subfertile patients, the prevalence of uterine and endometrial abnormalities (endometrial polyps or irregularities, uterine myomas including submucous one) was 22%, whereas congenitally maldeveloped uteri were detected in 3.8% of women undergoing ART (using 3D U/S) which may have a negative impact on ART outcome.